Factors associated with adolescent and caregiver reported problems in using asthma medications. (3rd April 2019) - Sleath, Betsy; Carpenter, Delesha M.; Walsh, Kathleen E.; Davis, Scott A.; Hayes Watson, Claire; Lee, Charles; Loughlin, Ceila E.; Garcia, Nacire; Reuland, Daniel S.; Tudor, Gail
ABSTRACT: Objectives : The purpose of this study was to: (a) describe the types of medication problems/concerns youth with asthma and their caregivers reported and (b) examine the association between sociodemographic characteristics and youth and caregiver reported medication problems/concerns. Methods : English- and Spanish-speaking youth ages 11–17 with persistent asthma were recruited at four pediatric clinics. Youth were interviewed and caregivers completed questionnaires about reported asthma medication concerns/problems. Multiple logistic regression was used to analyze the data. Results : Three hundred and fifty-nine youth were recruited. Eighty percent of youth and 70% of caregivers reported one or more problems in using asthma medications. The most commonly reported problems by youth were: (a) hard to remember when to take the asthma medication (54%) and (b) hard to use asthma medication at school (34%). Younger children were significantly more likely to report difficulty in understanding their asthma medication's directions and difficulty reading the print on the medication's package. Caregivers' top-reported problem was that it is hard for their child to remember to take their asthma medications (49%). Caregivers without Medicaid were significantly more likely to express difficulty paying for their child's asthma medications. Conclusions : Difficulty remembering to take asthma medication was a significant problem for youth and their caregivers. Providers should work with youth and their caregivers to identify asthma medication problems and discuss strategies to address those problems.